2021
DOI: 10.3390/biom11030374
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Effects on Genotoxicity in Diesel Exhaust Particles Exposed C57BL/6 Mice

Abstract: There is growing evidence that the accumulation of DNA damage induced by fine particulate matter (PM2.5) exposure is an underlying mechanism of pulmonary disease onset and progression. However, there is a lack of experimental evidence on whether common factors (age, gender) affect PM2.5 induced genomic damage. Here, we assessed the DNA damage potency of PM2.5 using conventional genotoxicity testing in old male and female mice aged 8 and 40 weeks. Mice were intratracheally instilled with diesel exhaust PM2.5 (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…53 Second, there are three important factors in human stroke studies related with final outcome unexplored in the present study that should be considered in the future: first, the relationship between infarct extension and the magnitude of clot formation/lysis changes under DEP-exposure conditions, second the impact of sex-differences in an in vivo scenario of clot formation (vs. our ex vivo study) where clot formation and lysis would be influenced by metabolic, genetic and vascular characteristics intrinsically different between biological sexes 54 57 and third, the influence of age as it has been recently reported that age increases DNA damage in DEP-exposed mice and it is known to be a key factor for stroke outcome and related to neuroprotectant or recanalization treatments. 52,58,59 Importantly, our results obtained from human cohorts match with those experimentally-produced in mouse models, but it should be noted that the sample size in the human cohorts is still small and results need further confirmatory studies in larger cohorts. In this regard, including other subjects representing other environmental urban areas such as green spaces or more heavily polluted areas would be desirable.…”
Section: Discussionsupporting
confidence: 67%
“…53 Second, there are three important factors in human stroke studies related with final outcome unexplored in the present study that should be considered in the future: first, the relationship between infarct extension and the magnitude of clot formation/lysis changes under DEP-exposure conditions, second the impact of sex-differences in an in vivo scenario of clot formation (vs. our ex vivo study) where clot formation and lysis would be influenced by metabolic, genetic and vascular characteristics intrinsically different between biological sexes 54 57 and third, the influence of age as it has been recently reported that age increases DNA damage in DEP-exposed mice and it is known to be a key factor for stroke outcome and related to neuroprotectant or recanalization treatments. 52,58,59 Importantly, our results obtained from human cohorts match with those experimentally-produced in mouse models, but it should be noted that the sample size in the human cohorts is still small and results need further confirmatory studies in larger cohorts. In this regard, including other subjects representing other environmental urban areas such as green spaces or more heavily polluted areas would be desirable.…”
Section: Discussionsupporting
confidence: 67%
“…Lee et al [ 2 ] investigated the age and gender effects of diesel exhaust particles (DEP) exposure on genotoxicity in C57BL/6 mice. They found that DEP exposure was not associated with an increase in the frequency of micronucleated polychromatic erythrocytes and did not induce systemic genotoxic effects in the bone marrow without an age effect but induced a significant increase in DNA damage in DEP-exposed mouse lung specimens in the comet assay with age.…”
mentioning
confidence: 99%